Promoting Companies and Host Community Relationship through Literacy Education for Sustainable Community Development in Rivers State, Nigeria. - UGWU, Angela Nkechi; OMEJE, Mercy Ebere (Advances in Social Sciences Research Journal, 2021)
There is need for a good rapport or relationship between companies and their host communities for a peaceful co-existence and maximum achievement of the company’s desired goals and development of the communities. This paper examined literacy education as a tool for equipping community members with skills, attitude and information for a peaceful co-existence between them and companies in their communities for sustainable community development. The writers established that there are conflicts that arise between companies and host communities due to reasons like ignorance, lack of information or misinformation that literacy programs can deal with. It was suggested among others that states should resuscitate mass literacy programmes in communities and there should be integration of literacy training programs into the community development plans by companies in their host communities as part of the cooperate social responsibilities